Transdermal enhancement through rat skin of luciferase plasmid DNA loaded in elastic nanovesicles - Aranya Manosroi (2018)
Transdermal absorption of luciferase plasmid (pLuc) was enhanced by loading in elastic cationic liposomes and niosomes and the application of iontophoresis or the stratum corneum (SC) stripping method. Cationic liposomes (DPPC/Chol/DDAB at a 1:1:1 molar ratio) and niosomes (Tween61/Chol/DDAB at a 1:1:0.5 molar ratio) were prepared by the freeze-dried empty liposomes method. The elastic vesicles were prepared by hydrating the lipid or surfactant film by 25% of ethanol instead of distilled water. Gel electrophoresis of all nanovesicles showed the 100% pLuc entrapment efficiency. All nanovesicles loaded with pLuc showed larger vesicular sizes than the nonloaded vesicles of about 1.4 times for liposomes and 1.7 times for niosomes. The nanovesicles loaded with pLuc demonstrated less positive zeta potential than the nonloaded vesicles. The pLuc loaded in elastic vesicles kept at 4 ± 2 and 27 ± 2°C for 8 weeks gave the remaining pLuc of about 70 and 60% for liposomes and 85 and 73% for niosomes, respectively. For nonelastic vesicles kept at 4 ± 2°C, 56 and 61% of the remaining pLuc were observed for liposomes and niosomes, respectively, while at 27 ± 2°C, all pLuc were degraded. The deformability indices of the elastic liposomes and niosomes loaded with the pLuc were 16.64 ± 2.92 and 20.72 ± 0.82, whereas the nonelastic vesicles gave 9.35 ± 0.09 and 10.08 ± 0.12, respectively. Transdermal absorption through rat skin pretreated with SC stripping or treated with iontophoresis of pLuc loaded in nanovesicles by vertical Franz diffusion cells was investigated at 37°C. The cells were stopped and the skin and the receiving solution were withdrawn at 1, 3, and 6 hours and the pLuc contents in the stripped SC, whole skin (viable epidermis and dermis; VED), and the receiving solution were assayed by the modified gel electrophoresis and gel documentation. Without the SC stripping technique or iontophoresis, the pLuc loaded and nonloaded in nonelastic cationic liposomes or niosomes were not found in SC, VED, and receiving solution. The fluxes in the whole skin of pLuc loaded in nonelastic liposomes and niosomes with SC stripping and iontophoresis at 6 hours gave 2.73 ± 0.46 and 3.83 ± 0.73, and 7.01 ± 1.22 and 9.60 ± 1.31 g/cm2/h, respectively, while pLuc loaded in elastic liposomes and niosomes without the SC stripping and iontophoresis at 6 hours showed 2.79 ± 0.09 and 2.84 ± 0.04 g/cm2/h, respectively. The pLuc loaded in elastic niosomes or in nonelastic niosomes with iontophoresis was found in the receiving solution with a higher amount than that loaded in elastic liposomes or nonelastic liposomes with iontophoresis. The fluxes in the receiving solution of pLuc loaded in nonelastic liposomes and niosomes with iontophoresis at 6 hours were 6.71 ± 0.31 and 8.82 ± 0.28 g/cm2/h, respectively. For elastic liposomes and niosomes, the fluxes of the loaded pLuc in the receiving solution were the same, at about 1.9 g/cm2/h. Although pLuc loaded in nonelastic niosomes with iontophoresis gave the highest delivery of the plasmid in VED and receiving solution, a more promising applicable approach for gene delivery has been suggested to be the elastic niosomal systems, since no equipment is required. © 2009 Informa UK Ltd.